2017
DOI: 10.1111/jocn.13904
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the quality of life of haemodialysis patients according to symptom cluster

Abstract: The findings of this study are expected to lead to practical guidelines for addressing the symptoms experienced by haemodialysis patients, and they provide basic information for developing nursing interventions to manage these symptoms and improve the QOL of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 22 publications
3
22
1
1
Order By: Relevance
“…Factors influencing symptom experience were different in the two groups that Shim and Cho (2018) identified. The first group of patients (characterized by higher symptom burden than the second group) had higher prevalence of diabetes and was comprised of more females.…”
Section: Factors Associated With Symptom Clustersmentioning
confidence: 83%
See 1 more Smart Citation
“…Factors influencing symptom experience were different in the two groups that Shim and Cho (2018) identified. The first group of patients (characterized by higher symptom burden than the second group) had higher prevalence of diabetes and was comprised of more females.…”
Section: Factors Associated With Symptom Clustersmentioning
confidence: 83%
“…The authors found that two individual symptoms were interconnected across multiple symptom dimensions: restless leg cross loaded on three of the five clusters (fluid volume, neuromuscular, and psychological) and fatigue cross loaded across all five symptom clusters. Shim and Cho (2018) identified two subgroups of patients using a personcentered approach (LCA). Membership in Cluster 1 was characterized by higher physical and emotional symptom burden than Cluster 2 (Shim & Cho, 2018).…”
Section: Symptom Clustersmentioning
confidence: 99%
“…Participants from the present study were then assigned into the latent class that provided the highest probability of assignment (Linzer and Lewis, 2011). An example of LCA syntaxis with simulated data (aimed at facilitating the comprehension of latent class assignment) is included as Appendix I.…”
Section: Resultsmentioning
confidence: 99%
“…The assignation of participants into a corresponding group/class (sensitive, over-interpretative, or naïve) was performed by using a latent class analysis (LCA), available with R version 3.2.1 (package poLCA) (Linzer and Lewis, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Interventions targeting one or more symptoms may improve the HRQoL of those receiving HD (Shim & Cho 2018). When HRQoL is improved, there is also improvement in survival, response to treatment and fewer hospitalisations (Jankowska‐Polańska et al 2016).…”
Section: Introductionmentioning
confidence: 99%